Online peer feedback between colombian and new zealand fl beginners: a comparison and lessons learned (2015)
We report on an exploratory study comparing the performance as online tutors of two groups of beginner eleven-year-old students of English in Colombia and Spanish in New Zealand. The native speaker students of the foreign language the others were learning corrected paragraphs written by their peers. The feedback provided by each group of tutors was analyzed for (1) language corrected, (2) input on errors, and (3) types of feedback provided. We found that both Colombian and New Zealand tutors willingly provided corrections to their peers and used other feedback strategies to foster attention to linguistic form. The Colombian tutors identified a higher number of errors, but the New Zealanders provided more detailed comments. We draw lessons from the exploration.Éste es un estudio exploratorio en el que comparamos el desempeño como tutores-en-línea de dos grupos de niños de 11 años, principiantes en inglés en Colombia y español en Nueva Zelanda. Como nativos de la lengua extranjera que los otros aprendían, cada grupo corrigió párrafos de sus compañeros. Las correcciones se analizaron buscando (1) lenguaje corregido, (2) frecuencia y (3) tipos de correcciones. Encontramos que todos los tutores indicaron gustosamente correcciones a sus compañeros y utilizaron otras estrategias para llamar su atención hacia la forma del lenguaje. Los tutores colombianos identificaron más errores, pero los tutores neozelandeses produjeron comentarios más detallados. Concluimos extrayendo algunas lecciones de la exploración.